1975
DOI: 10.1177/153857447500900410
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysms of an Aorto-Coronary Artery Saphenous Vein Bypass Graft—A Case Report

Abstract: A 62 year old man with severe angina pectoris underwent aoroto-coronary saphenous vein graft implantation. After a four month asymptomatic period the patient underwent aorto-coronary graft angiography. Left anterior descending graft opacification demonstrated multiple venous aneurysmal dilations. The clinical significance of this finding is currently unknown but such saphenous vein disease warrants further investigation. Saphenous vein grafts have been utilized to replace or bypass obstructed and diseased peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Cases of SVG aneurysms have been reported since 1975 [17,18]. Saphenous vein graft aneurysms are often asymptomatic, even when their diameters are large, as in such 10-cm SVG aneurysm reported by Wight et al [19]; however, aneurysm rupture is not exceptional [11,12,13] and SVG aneurysm infection has been reported as well [20].…”
Section: Discussionmentioning
confidence: 94%
“…The few cases of early presentation of SVG aneurysm are attributed to an inherent weakness of the venous wall due to lack of circular muscle at the site of venous valves. 4 The cause of late-developing aneurysms is incompletely understood but believed to involve developing atherosclerosis and thrombus, 5,6 hyperlipidemia, 6 hypertension, as well as defects to the vein graft itself, 5 and trauma. 7 SVG aneurysms are often asymptomatic and many times are suspected because of an unusual chest x-ray.…”
Section: Discussionmentioning
confidence: 99%